The Toymaker - De Quidt, Jeremy; Blythe, Gary (Oxford New York David Fickling Books, 2010)
What good is a toy that will wind down? What if you could put a heart in one? A real heart. One that beat and beat and didn't stop. What couldn't you do if you could make a toy like that? From the moment Mathias becomes the owner of a mysterious piece of paper, he is in terrible danger.
Keywords: Toymakers -- Juvenile fiction; Toy making -- Juvenile fiction; Fantasy fiction; Children's stories